Pengaruh Kompensasi dan Motivasi Terhadap Kepuasan Kerja Pada Karyawan PT Supermal Karawaci - Ningrum, Nurul Amalia Tyas (Jurnal ATAMA, 2022)
This study aimed to determine the effect of compensation and motivation on job satisfaction at PT Supermall Karawaci. The sample in this study was 30 employees at PT Supermall Karawaci. The sampling technique used is the saturated sampling technique. Primary data was collected by distributing questionnaires, and secondary data was obtained from the company. The analytical technique used is multiple linear regression analysis using SPSS version 26 software. The results showed that partially the compensation variable (X1) had a significant effect on job satisfaction (Y). T count indicates this> t table, i.e., 3.348 > 2.04841, Motivation (X2) has a significant effect on job satisfaction (Y). T count indicates this> t table which is 2.262 > 2.04841; the significant regression value is 0.002, and 0.032 is smaller than 0.050. And simultaneously, variable compensation (X1) and motivation (X2) have a positive effect on job satisfaction (Y), namely F count > F table of 26.590 > 3.354. With multiple linear regression equation value Y = 5.246 + 0.543 X1 +0.303 X2. With a coefficient of determination of 66.3%. At the same time, 33.7% were from other variables that were not studied.